Letter from Hamilton Fyfe of Daily Herald to Poulton of GC, re: absence of general news in the British Worker
"Letter from Hamilton Fyfe of Daily Herald to Poulton of GC, re: absence of general news in the British Worker" [g0929001.jpg], n.d. TUC Organisation